Innovation is everybody's business : how to make yourself indispensable in today's hyper-competitive world - Tucker, Robert B., 1953-
"This is the only book on innovation written exclusively for frontline employees; all the other books on innovation explain organization-wide strategies--which can only be implemented by management. Global innovation speaker Robert Tucker explains how every frontline employee can innovate in their own job in important, valuable ways, by challenging assumptions, delighting customers, cutting costs, and more. No organizational initiative, R&D budget, or management approval required! The upside for the employee is that being innovative in your own job is the best way to make yourself indispensable. Master the seven essential "I-Skills" you need to make yourself indispensable. Unleash the "the mindset, skill-set and toolset of the innovator" that enable you to anticipate and rise to the challenges your organization faces in a hypercompetitive era. Build tools for work-life balance and creating your own job satisfaction. Innovation is Everyone's Business is a self-help book, a motivational book, a leadership book, a creativity book, and a team-building book all in one. It is among the first of a new sub-genre of titles on coping with a changing workplace--